Incidence of Recreational Alpine Skiing and Snowboarding Injuries: six years experience in the largest ski resort in Finland. (June 2015) - Stenroos, A.; Handolin, L.
Background and Aims: The aim of this study was to provide information on incidences and severity of recreational alpine skiing and snowboarding injuries in Northern Finland and to discuss possible preventive measures to reduce the number and severity of injuries in the future. Materials and Methods: This retrospective study consists of all injured skiers and snowboarders in the Levi Ski Resort during the 2006–2012 winter seasons. The Levi Ski Resort has a SKIDATA® system which records automatically every ski-lift run taking place. The emergency system of the resort registers the data (conditions during the injury, patient characteristics, and observed and/or suspected injuries) of all injured persons they meet. The severity of injury is defined by the needed level of care: Grade 1 (treated by the emergency system with no need for further referral), Grade 2 (referral to the local primacy care clinic), Grade 3 (transfer to hospital by ambulance), and Grade 4 (transfer to tertiary care by helicopter). Results: During the 6-year study period, there were 29, 576.132 lift runs and 2911 injuries were met by the emergency system, resulting in the average injury incidence of 0.98 injuries per 10, 000 lift runs. Vice versa, the average number of the ski-lift rides needed to generate one injury was 10, 160. The knee injuries of the skiers constituted almost one-third of all cases, whereas snowboarders sustained more injuries to the upper limb and axial areas. Conclusion: Skiing and snowboarding are related to a relatively high risk of injury. The most common injuries affect the knee in skiers and the upper extremity, especially the wrist, in snowboarders. A continuous and systematic review of injuries is needed to monitor the effects of changes made in terms of the safety.